Reducing Routing Overhead In MANET Using NCPR (International Journal of Engineering and Computer Science, 2014)
Mobile ad hoc network consists of a group of mobile nodes which can be dynamically self-organized into arbitrary topology networks without any fixed infrastructure. In MANET mobile nodes will not stay in a same position, due to this large mobility of nodes in MANET, frequent link breakages will occur which will lead to path failure and route discovery problems. To overcome this type of routing overhead we are proposing the new technique using NCPR. The proposed NCPR method is used to determine the rebroadcast delay in the rebroadcast order and obtain the more exact additional coverage ratio by sensing neighbor coverage knowledge.